Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Wajib Pajak Terhadap Penggunaan E-Filing - Lavenia Herawan; Waluyo Waluyo (Ultima Accounting : Jurnal Ilmu Akuntansi, 2014)
The purpose of this research is to analyze the influence of perceived usefulness, perceived ease of use, security and privacy to the use of e-Filing. The object of this research is the individual taxpayer who uses e-Filing and registered in the Tax Office (KPP) Pratama Kosambi.. This research used primary data in the form of questionnaires were 117 pieces. The method used in this research is the causal study and the sampling technique that used is convenience sampling. The method that used is multiple regression analysis. The results of this study indicate that: (1) perceived usefulness has influence on the use of e-Filing, (2) perceived ease of use has influence on the use of e-Filing, (3) the security and privac has influence on the use of e-Filing, (4) perceived usefulness, perceived ease of use, security and privacy have influence simultaneously on the use of e-Filing. Keywords: perceived usefulness, perceived ease of use, security and privacy, the use of Filing